1984
DOI: 10.1055/s-0038-1661181
|View full text |Cite
|
Sign up to set email alerts
|

The Contact Phase of Blood Coagulation in Diabetes Mellitus and in Patients with Vasculopathy

Abstract: SummaryThe contact phase has been studied in diabetics and patients with macroangiopathy. Factor XII and high molecular weight kininogen (HMWK) are normal. C1-inhibitor and also α2-macroglobulin are significantly elevated in diabetics with complications, for α1-macroglobulin especially in patients with nephropathy, 137.5% ± 36.0 (p <0.001). C1-inhibitor is also increased in vasculopathy without diabetes 113.2 ± 22.1 (p <0.01).Prekallikrein (PK) is increased in all patients’ groups (Table 2) as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 1 publication
1
9
2
1
Order By: Relevance
“…Our study confirms earlier observations [3,12] that variables of the contact phase of coagulation may exhibit different patterns in diabetics with different complications. A discriminant function with Cl-inhibitor concentration, HK activity and fibrinogen as most decisive variables strongly separated diabetics with neuropathy from those without complications or with angiopathy alone.…”
Section: Discriminant Analysis Between the Clinical Groupssupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirms earlier observations [3,12] that variables of the contact phase of coagulation may exhibit different patterns in diabetics with different complications. A discriminant function with Cl-inhibitor concentration, HK activity and fibrinogen as most decisive variables strongly separated diabetics with neuropathy from those without complications or with angiopathy alone.…”
Section: Discriminant Analysis Between the Clinical Groupssupporting
confidence: 92%
“…In a previous study from our laboratory concerning different hemostatic functions of plasma and platelets in patients with diabetes mellitus and their c o n t r i b u t i o n to diabetic complications such as neuropathy, micro-and m a c r o a n g i o p a t h y and n e p h r o p a t h y [2,3,7], we found that high prekallikrein values seemed to characterize a small group of patients with sensomotor neuropathy. The aim of the present study was to investigate the relationship between diabetic complications, especially neuropathy, and the contact-activation phase of coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of fibronectin and vWf are considered markers of endothelial injury and associated with glomerular disease in diabetes [37±40]. a-2 macroglobulin is increased in patients with diabetic complications [41,42]. Moreover, fibrinogen, vWf, F VII:C, and factor VIII (a liver synthesized protein bound to vWf in the circulation) are associated with a higher incidence of ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing number of studies has focussed attention on fibrinogen in diabetes, suggesting its role as a marker of cardiovascular risk also in this disease. An association between initial hyperfibrinogenaemia and the subsequent occurrence of macroangiopathy, as well as the evidence that a high fibrinogen concentration enhances the risk of cardiovascular disease in diabetic patients, have been reported [3][4][5]. The demonstration that diabetes and parental history of diabetes are strongly and positively associated with fibrinogen levels has also been made [6].…”
Section: Fibrinogen and Diabetesmentioning
confidence: 99%